2009
DOI: 10.1016/j.buildenv.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving comfort levels in a traditional high altitude Nepali house

Abstract: Humla Province is a remote mountainous region of northwest Nepal. The climate is harsh and the local people are extremely poor. Most people endure a subsistence culture, living in traditional housing. Energy for cooking and heating comes from fuelwood, supplies of which are diminishing. In order to improve the indoor environment and reduce fuelwood use, smokeless stoves are being introduced to replace the open fire in Humli homes. There is some concern, however, that comfort levels may not be as acceptable wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…The physical properties of air change as the altitude increases, leading to lower air pressure, density, temperature, humidity, and heat transfer coefficient, and a higher radiation [190][191][192][193][194]. Greenhouses are considered a tool to provide enough vegetables in high-altitude areas, but there are limited relevant studies [195][196][197], and further investigations are necessary.…”
Section: More Variables Considered In Ventilation Modelsmentioning
confidence: 99%
“…The physical properties of air change as the altitude increases, leading to lower air pressure, density, temperature, humidity, and heat transfer coefficient, and a higher radiation [190][191][192][193][194]. Greenhouses are considered a tool to provide enough vegetables in high-altitude areas, but there are limited relevant studies [195][196][197], and further investigations are necessary.…”
Section: More Variables Considered In Ventilation Modelsmentioning
confidence: 99%
“…Pandey et al [14] conducted research on domestic smoke pollution and acute respiratory infections in Nepal and found that episodes of moderate and severe acute respiratory infections increased with an increase in the level of exposure to domestic smoke pollution. Fuller et al [15] used measured firewood and temperature data to validate a simple and cost-effective model of rural houses. Some other studies have highlighted the firewood use patterns associated with socio-economic factors and CO 2 emissions [16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ryu et al [58] quantitatively analyzed the characteristics of the wind flowing through a semi-open space with a wooden floor located between the front and back yards of traditional Korean residences. In Nepal, creating a sun space at the entrance of traditional Humla homes was recommended as a means of reducing the use of firewood in winter and improving thermal comfort [59]. In Pol House, a traditional residence in the Indian city of Ahmedabad, some techniques such as improving the thermal insulation of walls and roofs, seasonal shades for windows and courtyards, and using mechanical fans were examined from the perspective of energy saving and thermal comfort [60].…”
Section: Introductionmentioning
confidence: 99%